The Effect of Breeders’ Capability Deprivation and Capability on Their Freedomof Choice - Sakuntalawati, Ratna Devi; Darsono, Darsono; Kartono, Drajat Tri; Slamet, Yulius (Advances in Social Sciences Research Journal, 2017)
Abstract This research aimed to evaluate the freedom of choosing opportunity by breeders in Getasan, Semarang Regency, Central Java Province, Indonesia. The preceding issue is that the breeders do not have capability of selling their product (milk) themselves to the collector cooperatives, and IPS (Dairying Industry). Breeders encounter capability deprivation because as producer, they should determine the selling price. The breeders do not have freedom of choice in the term of milk marketing chance. This research used survey method and the population was milk cow breeders. The sample of village was taken using cluster sampling and that of breeder respondents using stratified random sampling techniques to determine the number of breeders for each selected villages. The village sample consisted of 3 villages and the respondent consisted of 375 breeders. There were 3 (three) variables in this research: breeders’ capability deprivation, capability, and freedom of choice. The data was analyzed using Path Analysis with SEM ordinary least square method. The result of research showed that there were a direct effect of breeders’ capability deprivation on the freedom of choice and an indirect effect through breeders’ capability. Keywords: Capability Deprivation, Capability, Freedom of Choice, Breeders.